N=1 SUSY backgrounds with an AdS factor from non-Abelian T duality - Araujo, Thiago R. [UNESP]; Nastase, Horatiu [UNESP] (Amer Physical Soc, 2015)
We consider the action of a non-Abelian T duality on backgrounds with an AdS(5) factor in type IIA supergravity, finding a new type IIB background, as well as the non-Abelian T-dual of a domain wall solution which has as limits the non-Abelian T-dual of AdS(5) x T-1,T-1 and the non-Abelian T-dual of AdS(3) x R-2 x S-2 x S-3. We explore some consequences of non-Abelian T duality for the dual conformal field theories.